Antimony exposure affects oocyte quality and early embryo development via excessive mitochondrial oxidation and dysfunction - Xia Wang; Xue Wu; Wei Ma; Qingxin Wang; Yuqi Chen; Xinyuan Zhao; Yajuan Lu (Ecotoxicology and Environmental Safety, 2024)
Antimony (Sb) is a metalloid, widely presents in the environment and associates with human health. In this study, we aimed to decipher whether Sb exposure is harmful to female reproduction and explore the underlying mechanisms. The ICR mice were exposed to 0, 5, 10, and 20 mg/kg acetate potassium Sb tartrate trihydrate by intraperitoneal injection for 10 days, then mouse oocytes were collected for further analysis. We first found a significant decrease in the proportion of MII-stage oocytes obtained from supernumerary ovulation in the fallopian tubes and early embryo development under Sb treatment. Then a series of tests showed Sb affects oocyte maturation by damaging the cytoskeleton of microtubule and actin. Moreover, the abnormal distribution of cortical granules and their component Ovastacin in oocytes, combined with reduced expression levels of Juno, affected sperm-oocyte binding and led to fertilization failure. Based on the sequencing results and experimental validation, it was demonstrated that Sb exposure impairs mitochondrial distribution and membrane potential, elevated levels of mitochondrial superoxide, finally caused energy supply deficits. Mitochondrial damage in oocytes after Sb exposure results in the excessive oxidative stress and early apoptosis. Taken together, these data suggest that Sb exposure decreases oocyte quality and female fertilization ability by impairing mitochondrial function and redox perturbation.